1)What should be taken away from
to obtain
Answers
Answered by
1
3x2 − 4y2 + 5xy + 20) − p = − x2 − y2 + 6xy + 20
p = (3x2 − 4y2 + 5xy + 20) − (− x2 − y2 + 6xy + 20)
= 3x2 − 4y2 + 5xy + 20 + x2 + y2 − 6xy − 20
= 3x2 + x2 − 4y2 + y2 + 5xy − 6xy + 20 − 20
= 4x2 − 3y2 − xy
p = (3x2 − 4y2 + 5xy + 20) − (− x2 − y2 + 6xy + 20)
= 3x2 − 4y2 + 5xy + 20 + x2 + y2 − 6xy − 20
= 3x2 + x2 − 4y2 + y2 + 5xy − 6xy + 20 − 20
= 4x2 − 3y2 − xy
radha2210:
is it 3y square what you have written in ur answer
Similar questions